Experiences of Batswana women diagnosed with both HIV/AIDS and cervical cancer - T. Molefe; S.E. Duma (AOSIS, 2009)
The central phenomenon of interest to the authors was the experiences of Batswana women who have been diagnosed with both HIV/AIDS and cervical cancer. They wanted to know how these women and their families coped with the burden of the two 'fatal' diseases. This interest was brought about by the current surge in cervical cancer cases in the country, and the relationship between the two diseases. There is scant literature on the experiences of women with the dual diagnosis of HIV/AIDS and cervical cancer. The purpose of the study was to explore the experiences of Batswana women who are diagnosed with both HIV/AIDS and cervical cancer. The research question was 'What are the experiences of Batswana women diagnosed with both HIV/AIDS and cervical cancer?' A phenomenological descriptive qualitative research design was therefore appropriate to answer the research question. Semi-structured interviews and field notes were used to collect data. One-to-one interviews were conducted with six women diagnosed with the two diseases. Both convenience and purposive sampling techniques were used in selection of participants. The seven procedural steps proposed by Collaizi (1978) were utilized in data analysis as the study was based on the phenomenology approach. The findings revealed that HIV/AIDS and cervical cancer are chronic illnesses that can instill chronic emotional pain. Reactions to diagnosis with these diseases include pain, fear or intense sadness. Coping with these conditions can be facilitated by different strategies such as acceptance, having hope, support from others and positive thinking. Support can come from children, family members, informal or formal groups and health service providers.